Visiting George And Patricia Kamp In Sun Valley, Nevada - Watkins, Howard::::::::: (1982)
Howard Watkins, Adam Watkins, Tyson Leatherwood; Back Row: Larry Leatherwood, Sherry, George Kamp, Christine Watkins, Patricia Kamp George's 58th birthday